2021
DOI: 10.1097/hjh.0000000000002968
|View full text |Cite
|
Sign up to set email alerts
|

Independent relationships between renal mechanisms and systemic flow, but not resistance to flow in primary hypertension in Africa

Abstract: Whether renal mechanisms of hypertension primarily translate into increases in systemic vascular resistance (SVR) in all populations is uncertain. We determined whether renal mechanisms associate with either increases in SVR (and impedance to flow) or systemic flow in a community of African ancestry.Method: In a South African community sampled across the full adult age range (n ¼ 546), we assessed stroke volume (SV), peak aortic flow (Q), SVR, characteristic impedance (Zc) and total arterial compliance (TAC) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The main findings of the present study are as follows: In a large (n ¼ 669) community sample in Africa, recently demonstrated to show a striking contribution of age-dependent, renal-related increases in systemic blood flow to PP and SBP in hypertension [6][7][8], we compared the intrafamilial aggregation and heritability of systemic flow to that of the vascular determinants of PP and hence SBP. In this regard, in-line with conventional physiological principles, and the 'Windkessel' model of the systemic circulation, PP in the brachial pulse is determined by the product of flow (Q) and the resistance to flow in a pulsatile system (Z c ) with an additional contribution from arterial compliance.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The main findings of the present study are as follows: In a large (n ¼ 669) community sample in Africa, recently demonstrated to show a striking contribution of age-dependent, renal-related increases in systemic blood flow to PP and SBP in hypertension [6][7][8], we compared the intrafamilial aggregation and heritability of systemic flow to that of the vascular determinants of PP and hence SBP. In this regard, in-line with conventional physiological principles, and the 'Windkessel' model of the systemic circulation, PP in the brachial pulse is determined by the product of flow (Q) and the resistance to flow in a pulsatile system (Z c ) with an additional contribution from arterial compliance.…”
Section: Discussionmentioning
confidence: 93%
“…However, in the present population, the increases in systemic flow are attributed to an age-related, volume-dependent increase in left ventricular preload (Frank-Starling effect) [6]. The presence of an age-related volume-dependent increase in systemic flow is supported by strong relations of systemic flow with age-related increases in left ventricular end diastolic volume, an age-related reduction in circulating renin concentrations and both age-related and nonagerelated alterations in several indices of renal tubular function [6,8]. In contrast, no relationships between systemic flow and ejection fraction are noted in this population [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations